Numerical studies of premixed hydrogen/air flames in a small-scale combustion chamber with varied area blockage ratio. (26th May 2020) - Elshimy, M.; Ibrahim, S.; Malalasekera, W.
Abstract: The increasing use of hydrogen as a renewable source of energy underlines the need to be able to assess the safety risks involved in the event of an accidental explosion. This paper presents numerical studies for hydrogen/air propagating flames at an equivalence ratio of 0.7 in a laboratory-scale combustion chamber equipped with turbulence generating baffles and a solid square cross section obstruction. The large eddy simulation (LES) modelling technique is used with an in-house computational fluid dynamics (CFD) model for compressible flows to study the flow turbulence and the flame propagation characteristics. The study is carried out using four different baffle arrangements and two different solid obstructions with area blockage ratios of 0.24 and 0.5. Results for the generated peak overpressure and the timing at which it occurs following ignition are considered as the primary safety factors. The time histories of the flame speed and position relative to the ignition source are validated against published experimental data. Good agreement is obtained between numerical results and experimental data which enables further predictions where measurements are limited in the study of vented hydrogen explosions. It was concluded that adding successive baffles and increasing the area blockage ratio escalates the maximum rate at which pressure rises and raises the generated peak explosion overpressure. Highlights: Characteristics of vented hydrogen explosions with various obstacle configurations. Effects of an increased area blockage ratio on hydrogen flames. Increased sensitivity of hydrogen to obstructions and area blockage ratio when compared to propane. Influence of area blockage ratio, number and location of obstacles on overpressure.